Lebih dari Sekadar Aturan: Kontribusi Persepsi Tarif Pajak Terhadap Kepatuhan - Dhiva Ismi Fauziah; Antin Okfitasari; Ety Meikhati (Universitas Duta Bangsa Surakarta, 2025)
This study examines the impact of government regulations and perceived tax rates on taxpayer compliance levels in Surakarta. Through a quantitative survey of 100 individual and corporate taxpayers at the Surakarta Tax Office (KPP Pratama), data were analyzed using multiple linear regression. The findings indicate that both factors have a significant positive effect. However, perceived tax rates (?=0.587) were found to have a stronger impact than government regulations (?=0.229) in driving compliance. This implies that taxpayers' subjective assessments of the fairness of rates are a stronger driver of compliance. The practical implication is that tax authorities need to prioritize building positive perceptions through transparency and fairness, in addition to enforcing clear and consistent regulations, to improve taxpayer compliance.